The Influence Of Implementation Firing Line Types Of Active Learning Model For The SMPN 2 Padang Science Students Grade VII - Mardiah Tajun; Rahmadhani Fitri; Mades Fifendy (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2017)
The purpose of this research is to know the influence of implementation of learning model of active learning type Firing Line to science learning result of grade VII SMPN 2 Padang on material classification of living creatures and matter. This research is based on problems at SMPN 2 Padang which is still dominated by teacher-centered learning so that the students knowledge is limited to the material was given by the teacher, so that students get bored faster during classroom learning process. This research was categorized into experimental research using Randomized Control Group Posttest Only Design. The sample of this research was chosen by purposive sampling method. The subjects of this research are two different classes; the first class is VII4 as the experimental class using learning model of active learning type Firing Line andVII5 as the control class using conventional of learning. Data of students learning outcomes were analyzed by using t-test analysis. The result of the research are according to the learning outcomes which is using t-test it showed that the learning outcomes of experimental group is better than control group with thitung(4,42) ˃ ttabel(1,67) which means the research hypothesis is accepted and student activities show that learning process using the learning model of Active Learning is better with percentage 77% than the conventional of learning with percentage 75%.